2020
DOI: 10.1111/dom.14017
|View full text |Cite
|
Sign up to set email alerts
|

Can the cardiovascular risk reductions observed with empagliflozin in the EMPA‐REG OUTCOME trial be explained by concomitant changes seen in conventional cardiovascular risk factor levels?

Abstract: Aim:The EMPA-REG OUTCOME trial demonstrated a significant reduction in cardiovascular (CV) outcomes in patients with type 2 diabetes given empagliflozin, a selective sodium-glucose cotransporter-2 inhibitor. We performed post-hoc analyses of this trial examining the degree to which empagliflozin-induced changes in conventional CV risk factors might explain the observed CV benefits. Materials and methods:We estimated three-year EMPA-REG OUTCOME CV event rates using a type 2 diabetes-specific clinical outcomes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…How SGLT2is exert their remarkable effects on CV and renal outcomes is not fully understood. For example, only 12% of the relative risk reduction for all-cause death caused by SGLT2is could be explained by the combined changes in conventional CV risk factors ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…How SGLT2is exert their remarkable effects on CV and renal outcomes is not fully understood. For example, only 12% of the relative risk reduction for all-cause death caused by SGLT2is could be explained by the combined changes in conventional CV risk factors ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous basic studies have reported that dapagliflozin reduced the sympathetic marker and suppresses prolonged ventricular repolarization [ 46 , 47 ]. Indeed, SGLT2 inhibitors have been shown to affect several other common modifiable risk factors and comorbidities associated with cardiovascular diseases, such as BW, renal function, uric acid level, and plasma lipid level [ 1 3 , 48 , 49 ]. Taken together, the results of the present study were comparable with those of previous studies [ 1 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In two post hoc analyses of EMPA‐REG OUTCOME data, simulation of the effects of empagliflozin compared with placebo on conventional CVD risk factors accounted for only 15% and 37% of the observed reduction in HHF risk observed in patients with T2DM and CVD. 54 , 55 …”
Section: Resultsmentioning
confidence: 99%
“…In two post hoc analyses of EMPA-REG OUTCOME data, simulation of the effects of empagliflozin compared with placebo on conventional CVD risk factors accounted for only 15% and 37% of the observed reduction in HHF risk observed in patients with T2DM and CVD. 54,55 A plethora of mechanisms outside of changes in conventional CVD risk factors have been proposed for how SGLT2is may improve HF outcomes (Figure 3A). However, not all have been the focus of RCT studies, which are reviewed in the following sections.…”
Section: Conventional Cardiovascular Disease Risk Factorsmentioning
confidence: 99%